Amassing of Cold Thermal Energy by Utilizing Phase Shift Material: A Review. Issue 1 (April 2021) - Chandrasekaran, P; Sivakumar, B
Abstract: Storing of cold energy is a predominant area in the cold thermal energy storage system in which the PCM plays a major role in hosting this energy storage process. This study fetches an encyclopedic review based on the current and erstwhile research in the field of cold energy storage using PCM. This dissertation provides an expansive view of the PCM solidification with the methodology of reducing the sub-cooling with the ramping up of heat flow rate besides of variegated nano-particulate and with protrusions. The effect of the fill volume of PCM in solidification is also delineated and how the size and material of PCM containment plays a role in solidification is also scrutinized and eventually, the application area of PCM cold storage is also explored.